2021
DOI: 10.1021/acs.organomet.1c00238
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable Rare-Earth Metal Complexes Supported by Chelating Silylene Ligands

Abstract: The use of N-heterocyclic silylenes (NHSi) as ligands is a rapidly developing field. However, only a handful of f-element silylene complexes have been disclosed so far. Herein, we report the synthesis and characterization of a series of thermally stable divalent and trivalent rare-earth metal complexes bearing the bis(silylene) LSiFcSiL (L = PhC(NtBu) 2 , Fc = ferrocenediyl) and the mono(silylene) L N Si (N = 2-(methylamido)pyridine). For the bis(silylene) LSiFcSiL ligand, the divalent complexes [Ln{N-(SiMe 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
(110 reference statements)
3
6
0
Order By: Relevance
“…Complex 1 crystallizes in the centrosymmetric monoclinic space group P 2 1 / c and the geometry around the calcium center is distorted tetrahedral (τ=0.74) [9] . The Ca−Si(II) bond length of 3.0632(8) Å is comparable to that found in the structurally related divalent Yb silylene complex (Yb−Si(II) 3.0766(7) Å), [10] which is consistent with the very close ionic radii of Ca 2+ and Yb 2+ [11] . The calcocene silylene complex B (3.2732(5) Å) and the bis(silylene) ligated Ca silylamide E (3.1646(8) and 3.2080(9) Å) have considerably longer Ca−Si(II) bonds (Figure 1).…”
Section: Figuresupporting
confidence: 70%
“…Complex 1 crystallizes in the centrosymmetric monoclinic space group P 2 1 / c and the geometry around the calcium center is distorted tetrahedral (τ=0.74) [9] . The Ca−Si(II) bond length of 3.0632(8) Å is comparable to that found in the structurally related divalent Yb silylene complex (Yb−Si(II) 3.0766(7) Å), [10] which is consistent with the very close ionic radii of Ca 2+ and Yb 2+ [11] . The calcocene silylene complex B (3.2732(5) Å) and the bis(silylene) ligated Ca silylamide E (3.1646(8) and 3.2080(9) Å) have considerably longer Ca−Si(II) bonds (Figure 1).…”
Section: Figuresupporting
confidence: 70%
“…Thus, resulting in the dimeric structure of 1 . The La–Si bond length is about 0.1 Å longer than in another reported La silylene complex (3.1868(8) Å), 18 even though a direct comparison of the bond lengths is hampered due to the distinct characteristics of dianionic silole compared to neutral silylene ligands and the different coordination numbers of both species. NMR spectra of 1 were recorded in THF-d 8 .…”
mentioning
confidence: 58%
“…The silanide signals are doublets from coupling to 89 Y ( 1 : δ Si = 12.86 ppm, 1 J YSi = 90.4 Hz; 2 : δ Si = 33.53 ppm, 1 J YSi = 88.9 Hz; 3 : δ Si = −148.54 ppm, 1 J YSi = 67.9 Hz), with the coupling constants comparable to those previously reported for yttrium silanide complexes, for example, [Y(Cp*) 2 {SiH(SiMe 3 ) 2 }] (δ Si = −120.00 ppm, 1 J YSi = 92 Hz) 13 and [Y{Si(SiMe 3 ) 2 R}(I) 2 (THF) 3 ] (R = Et, δ Si = −73.50 ppm, 1 J YSi = 71.0 Hz; SiMe 3 , δ Si = −134.68 ppm, 1 J YSi = 63.4 Hz), 14 and greater than those seen for the yttrium silylenes [Y(Cp) 3 {Si[{N(CH 2 t Bu)} 2 C 6 H 4 -1,2]}] (δ Si = 119.5 ppm, 1 J YSi = 59 Hz) 19 and [Y{N(SiHMe 2 ) 2 } 3 {Si[(N t Bu) 2 CPh][C 5 H 4 N(NMe-2)]-κ 2 Si , N }] (δ Si = 9.4 ppm, 1 J YSi = 55 Hz). 20 The positive δ Si values for alkyl-substituted silanides and negative values for the silyl-substituted silanides, together with larger metal–silicon coupling constants for the former ligand sets, arise from alkyl substituents being more electron-donating than their silyl counterparts, which additionally exhibit negative hyperconjugation. 12 , 35 These data are in accord with previous observations on related Yb(II) silanide complexes containing I = 1/2 171 Yb nuclei (e.g., [Yb(Si t Bu 2 Me) 2 (THF) 3 ]: 21 δ Si = 29.24 ppm, 1 J YbSi = 921 Hz; [Yb(Si t Bu 3 ) 2 (THF) 2 ]: 21 δ Si = 54.19 ppm, 1 J YbSi = 976 Hz; [Yb{Si(SiMe 3 ) 3 } 2 (THF) 3 ]: 35 δ Si = −144.8 ppm, 1 J YbSi = 723 Hz).…”
Section: Resultsmentioning
confidence: 99%
“…6−10 However, in recent years, an increasing number of RE silicon complexes have been prepared, and more comprehensive characterization is being performed in order to better understand their electronic structures and to inform future applications. 11,12 For yttrium silicon chemistry, structurally authenticated complexes containing Y−Si bonds that have been reported to date include [Y(Cp*) 2 {SiH(SiMe 3 ) 2 }] (Cp* = C 5 Me 5 ), 13 [Y{Si(SiMe 3 ) 2 R}(I) 2 (THF) 3 ] (R = Et or SiMe 3 ), 14 [Y{Si-(SiMe 2 H) 3 } 2 (OEt 2 )(μ 2 -Cl) 2 (μ 3 -Cl)K 2 (OEt 2 ) 2 ] ∞ , 15 20 Recently, we showed that a combination of 29 Si-{ 1 H} NMR spectroscopy and density functional theory (DFT) calculations could be applied to quantify covalency in diamagnetic Yb(II)−Si bonds, allowing comparisons with Mg(II), Ca(II), and in silico-calculated No(II) homologs. 21 To potentially extend this methodology to the predominant +3 oxidation state for RE ions, we are currently limited to diamagnetic closed shell Sc(III), Y(III), La(III), and Lu(III) examples; 3 recently, solid-state 29 Si{ 1 H} NMR spectroscopy has been used to study a series of La(III) silanide complexes, and coupling to 99.95% abundant I = 7/2 139 La nuclei was resolved.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation